A corpus-based pragmatic analysis of Jordanians Facebook status updates during COVID-19 - Hadeel Abdalhadi; Nisreen Al-Khawaldeh; Anas Al Huneety; Bassil Mashaqba (Ampersand, 2023)
This study investigates the communicative functions of status updates on Facebook during COVID-19. For this purpose, a corpus of 500 status updates was collected from 100 Facebook users for 90 consecutive days. Subsequently, the data were characterized into five speech acts drawing heavily on Searle's speech act framework, prominent among which are expressives and assertives. Data analysis revealed that status updates could be considered a substantial medium for understanding intended human communication. Various types of speech acts were used with different frequencies and percentages, although people were inclined mostly to use expressive speech acts. The sociocultural variations in conjunction with forming and constructing identities were reflected in the status updates manifested in the current situation of the pandemic, which makes Jordanians appear more humorous than before. This research is significant because studying aspects of a language helps in understanding the hidden motivations, beliefs, ideas, attitudes and identities along with the social, cultural, and political factors, which in turn provides logical solutions for certain problems.